Implementation of Safety Risk Management in Aircraft Airffame Maintenance - Wibowo, Untung; Engkus Kurniawan, Iwan; Prayitno, Hadi (Yayasan Sinergi Kawula Muda, 2023)
This study analyzes the application of Safety Risk Management in the practice of aircraft maintenance at AMTO (Aircraft Maintenance Training Organization) Indonesia Aviation Polytechnic Curug. The research method used is descriptive qualitative. Starting with hazard identification, risk assessment, and continuing with mitigation actions. Risk assessment uses the Risk Matrix. The results showed that 9 hazards were at tolerable levels, namely 4 hazards in the component release phase, 3 hazards in the inspection phase, and 2 hazards in the installation and adjustment phase. Recommended mitigation measures include additional training, safety briefing, safety promotion, supervision of important phases, and periodic checks on tools and equipment. This research is then used as a document for compliance with Safety Risk Management according to the SMS Implementation Plan at the AMTO (Aircraft Maintenance Training Organization) of the Indonesian Aviation Polytechnic Curug.